Change in Tongue Morphology in Response to Expiratory Resistance Loading Investigated by Magnetic Resonance Imaging - Horiuchi, Noriaki; Shuntoh, Hisato; Matsuo, Yoshimi; Yanagisawa, Yukio; Mitamura, Masaaki (Journal of Physical Therapy Science, 2013)
[Purpose] The purpose of this study was to investigate the effect of expiratory resistance load on the tongue area encompassing the suprahyoid and genioglossus muscles. [Subjects] The subjects were 30 healthy individuals (15 males, 15 females, mean age: 28.9 years). [Methods] Magnetic resonance imaging was used to investigate morphological changes in response to resistive expiratory pressure loading in the area encompassing the suprahyoid and genioglossus muscles. Images were taken when water pressure was sustained at 0%, 10%, 30%, and 50% of maximum resistive expiratory pressure. We then measured tongue area using image analysis software, and the morphological changes were analyzed using repeated measures analysis of variance followed by post hoc comparisons. [Results] A significant change in the tongue area was detected in both sexes upon loading. Multiple comparison analysis revealed further significant differences in tongue area as well as changes in tongue area in response to the different expiratory pressures. [Conclusion] The findings demonstrate that higher expiratory pressure facilitates greater reduction in tongue area.